Biologically Inspired Stretchable, Multifunctional, and 3D Electronic Skin by Strain Visualization and Triboelectric Pressure Sensing. Issue 1 (5th November 2021) - Li, Jing; Yuan, Zuqing; Han, Xun; Wang, Chunfeng; Huo, Zhihao; Lu, Qiuchun; Xiong, Meiling; Ma, Xiaole; Gao, Wenchao; Pan, Caofeng
Abstract : Electronic skins have been developed for sensing vertical pressure and tensile strain individually. Here, a stretchable, multifunctional, and 3D electronic skin (SMTE) is fabricated to imitate the squid's natural structure to achieve strain visualization and pressure sensing at the same time. The SMTE consists of an anisotropic and elastic light shutter to tune the natural color or fluorescence, which converts the in‐plane strain to the visual changes in color and intensity. The shutter also works as an elastic dielectric layer for vertical pressure sensing based on the principle of a single‐electrode triboelectric nanogenerator. The performance of the SMTE is demonstrated by integrating it on a model hand as a tactile sensor for touch, bending, and gesture interpretation, which has potential applications in human–machine interaction, soft robots, and artificial intelligence. Abstract : Inspired by the discoloration behavior of squids, a stretchable, multifunctional, and 3D electronic skin is designed to achieve strain visualization and pressure sensing. It converts the in‐plane strain into visual changes and the vertical pressure into electrical signals. This electronic skin has potential applications in human–machine interaction, soft robots, and artificial intelligence.